SOVEREIGNTY AND HUMAN RIGHTS - F. I. Valyarovskiy (Современная наука и инновации, 2022)
In this article the traditional problems of human rights and freedoms are considered in relation to state and national sovereignty, which allows us to take a new look at this problem, considering modern political and social trends.